2000
DOI: 10.2113/gscanmin.38.4.899
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosian Xenotime-(Y) From the Annie Claim #3 Granitic Pegmatite, Southeastern Manitoba, Canada: Evidence of the Tetrad Effect?

Abstract: Dysprosian xenotime-(Y) was found in the Annie Claim #3 pod of lepidolite-subtype granitic pegmatite within the Greer Lake intrusion of pegmatitic granite, in the Archean Bird River Subprovince of the Superior Province, in southeastern Manitoba. It occurs as microscopic inclusions in spessartine and as discrete crystals, both enclosed in ferroan muscovite, also associated with manganocolumbite -manganotantalite, microlite, zircon and apatite. The xenotime-(Y) contains up to 14.88 wt.% Dy 2 O 3 (and 7.59 wt.% G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…4,7 and 9). Similar phenomena have already been noted by many other researchers (Förster, 1998;Irber, 1999;Masau et al, 2000;Kempe and Götze, 2002). It is therefore reasonable to rule out the possibility that whole-rock samples acquire their convex tetrads during fractional crystallization.…”
Section: Magmatic Crystallization?supporting
confidence: 84%
“…4,7 and 9). Similar phenomena have already been noted by many other researchers (Förster, 1998;Irber, 1999;Masau et al, 2000;Kempe and Götze, 2002). It is therefore reasonable to rule out the possibility that whole-rock samples acquire their convex tetrads during fractional crystallization.…”
Section: Magmatic Crystallization?supporting
confidence: 84%
“…Some phosphate minerals may be rich in REEs. In xenotime, Y ions are often replaced by lanthanides with an emphasis on HREEs (Alex et al, 1998;Masau et al, 2000;Sabourdy et al, 1997). Monazite quite locally even forms bodies of economical importance (Forster, 1998), and apatites (fluoro-phosphates) may also contain REEs (Bauluz et al, 2000;Braun et al, 1993).…”
Section: Rees In Primary Minerals and Surface Soilsmentioning
confidence: 99%
“…However, subsequent studies by Bau (1997) and Irber (1999) demonstrated that the exact shapes and sizes of tetrads cannot be correctly reproduced by Rayleigh model calculations and that whole rock REE patterns with more than one rounded segment can only be obtained assuming unrealistic mineral assemblages. Furthermore, accessory minerals including garnet, monazite, xenotime, and apatite typically have REE patterns with tetrads similar to the related granitic rocks (Fö rster, 1998;Irber, 1999;Masau et al, 2000;Kempe and Gö tze, 2002) ruling out the possibility that whole rock samples acquire convex tetrads during fractional crystallization. Kawabe (1995), Irber (1999), and Dolejš and Š temprok (2001) proposed that the development of convex segments in whole rock REE patterns is caused by processes of fluidmelt interaction during crystallization of the silicate melt under open system conditions whereby a complementary REE pattern with concave tetrads is removed from the solidifying magma by coexisting (or exsolved) hydrothermal fluids.…”
Section: Introductionmentioning
confidence: 99%